Elite junior tennis players' perceptions of concentration skills - Young, J. (Medicine and Science in Tennis, 2008)
In a study commissioned by Tennis Australia, elite junior tennis players` attentional processes were examined. Sixteen girls aged 11 to16 years and fifteen boys aged 11 to 15 years, comprising an elite tennis squad training at the National Training Centre, were surveyed with a questionnaire. Responses to their understanding of concentration, ratings of the importance of key psychological attributes for success, thoughts prior to and during best and worst performances, ratings of the extent of focused attention and levels of motivation in best and worst performances were qualitatively and quantitatively analysed. Also analysed were responses to nominated sources of distractions and thoughts prior to choking in competitive matches. The study found in best performances, players were more process oriented prior to the start of performance, reported more broad-internal focus during play and between points, and were more intensely absorbed and motivated to win than in worst performances. Prior to the commencement of worst performances players were primarily outcome focused. Choking in competitive matches was associated with an internal focus in players. Results were interpreted in terms of Nideffer`s conceptualisation of attentional processes and outcome and process cues. Practical implications for training programs are highlighted.